2013
DOI: 10.1371/journal.pone.0059633
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Malaria by Enhanced Phagocytosis of Erythrocytes in LMP7-deficient Mice

Abstract: General cellular functions of proteasomes occur through protein degradation, whereas the specific function of immunoproteasomes is the optimization of antigen processing associated with MHC class I. We and others previously reported that deficiency in subunits of immunoproteasomes impaired the activation of antigen-specific CD8+ T cells, resulting in higher susceptibility to tumor and infections. We demonstrated that CD8+ T cells contributed to protection against malaria parasites. In this study, we evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…In line with previous reports from ourselves and others on the importance of the phagocytosis of infected RBCs in the protective response to blood-stage malaria ( Zhang et al, 1999 ; Couper et al, 2007 ; Imai et al, 2010 ; Matsuzaki-Moriya et al, 2011 ; Duan et al, 2013 ), mice depleted of macrophages by administration with clodronate/liposome (C/L) quickly died in association with high parasitemia ( Figure 7A,B ). It has also been reported that PS-exposing cells are highly susceptible to phagocytosis by macrophages ( Fadok et al, 1998 ; van den Eijnde et al, 1998 ).…”
Section: Resultssupporting
confidence: 91%
“…In line with previous reports from ourselves and others on the importance of the phagocytosis of infected RBCs in the protective response to blood-stage malaria ( Zhang et al, 1999 ; Couper et al, 2007 ; Imai et al, 2010 ; Matsuzaki-Moriya et al, 2011 ; Duan et al, 2013 ), mice depleted of macrophages by administration with clodronate/liposome (C/L) quickly died in association with high parasitemia ( Figure 7A,B ). It has also been reported that PS-exposing cells are highly susceptible to phagocytosis by macrophages ( Fadok et al, 1998 ; van den Eijnde et al, 1998 ).…”
Section: Resultssupporting
confidence: 91%
“…In a Leishmania major infection model, the absence of the subunit LMP7 had no effect on the ability of DCs to stimulate CD8 + T cells in both WT and LMP7 -/mice, as well as the authors showed similar IFNg production and T cell proliferation (51). The role of LMP7 was further highlighted in a malaria infection model, since the absence of LMP7 resulted in lower parasite growth, reduced parasite burden but an enhanced immune response with increased phagocytosis activity (52). LMP7 -/mice displayed reduced MHC I expression on APCs (53) and infected LMP2 -/mice showed a strong reduction (~70%) of CD8 + lymphocytes compared to WT mice (54).…”
Section: Discussionmentioning
confidence: 96%
“…Antibodies specific for parasite antigens and phagocytes play a major role in disrupting the erythrocytic cycle. Phagocytes, such as macrophages, engulf parasites and parasitized RBCs, and are required for the final clearance of malaria parasites [ 23 , 26 , 28 , 49 , 50 ]. Many studies have emphasized the role of antibodies in controlling parasitemia, and almost all malaria vaccines aim to induce specific antibodies [ 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%